Efficient Delivery of Hydrophilic Small Molecules to Retinal Cell Lines Using Gel Core-Containing Solid Lipid Nanoparticles - Li Huang; Erico Himawan; Soumaya Belhadj; Raúl Oswaldo Pérez García; François Paquet Durand; Nicolaas Schipper; Matej Buzgo; Aiva Simaite; Valeria Marigo (MDPI AG, 2021)
In this study, we developed a novel solid lipid nanoparticle (SLN) formulation for drug delivery of small hydrophilic cargos to the retina. The new formulation, based on a gel core and composite shell, allowed up to two-fold increase in the encapsulation efficiency. The type of hydrophobic polyester used in the composite shell mixture affected the particle surface charge, colloidal stability, and cell internalization profile. We validated SLNs as a drug delivery system by performing the encapsulation of a hydrophilic neuroprotective cyclic guanosine monophosphate analog, previously demonstrated to hold retinoprotective properties, and the best formulation resulted in particles with a size of ±250 nm, anionic charge > −20 mV, and an encapsulation efficiency of ±60%, criteria that are suitable for retinal delivery. In vitro studies using the ARPE-19 and 661W retinal cell lines revealed the relatively low toxicity of SLNs, even when a high particle concentration was used. More importantly, SLN could be taken up by the cells and the release of the hydrophilic cargo in the cytoplasm was visually demonstrated. These findings suggest that the newly developed SLN with a gel core and composite polymer/lipid shell holds all the characteristics suitable for the drug delivery of small hydrophilic active molecules into retinal cells.